Evaluasi Kualitas Air Minum di Kampus Universitas Siliwangi Menggunakan Parameter Fisika, Kimia, dan Mikrobiologi - Visi Tinta Manik; Erviyana Windiastuti; Suci Apsari Pebrianti (Jurnal Serambi Engineering, 2024)
Every person has a fundamental need to drink water. However, the environment today presents conditions—like the clean water crisis—that every person needs to be aware of. Compared to other water demands, drinking water must meet strict quality standards because it will enter the body. As a result, in order to assess the drinking water quality in the vicinity of Siliwangi University Tasikmalaya using Peraturan Menteri Kesehatan Republik Indonesia Nomor 492/MENKES/PER/IV/2010, research must be conducted. In this investigation, three types of water samples were collected from a single drinking water source: spring water, filtered water, and water that has undergone ultraviolet (UV) light processing. In this investigation, chemical, physical, and biological characteristics were taken into consideration. The three samples' chemical and physical parameters results surpass the quality standards. Nevertheless, the three samples did not comply with the standard of quality microbiologically.